2014
DOI: 10.1155/2014/707095
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and Canopy Characteristics of Different Varieties at the Early Elongation Stage and Their Relationships with the Cane Yield in Sugarcane

Abstract: During sugarcane growth, the Early Elongation stage is critical to cane yield formation. In this study, parameters of 17 sugarcane varieties were determined at the Early Elongation stage using CI-301 photosynthesis measuring system and CI-100 digital plant canopy imager. The data analysis showed highly significant differences in leaf area index (LAI), mean foliage inclination angle (MFIA), transmission coefficient for diffused light penetration (TD), transmission coefficient for solar beam radiation penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
1
11
0
2
Order By: Relevance
“…Such change ultimately reduces gaseous exchange causing perturbed photosynthetic activity and instigating low sink production. It can also be presumed that the low cane yield of high sugar content genotypes maybe because of the decimal behavior of stomata caused by high sucrose content 52 . The role of genotypic makeup against response to doses of radiation was evident from the varying response of genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Such change ultimately reduces gaseous exchange causing perturbed photosynthetic activity and instigating low sink production. It can also be presumed that the low cane yield of high sugar content genotypes maybe because of the decimal behavior of stomata caused by high sucrose content 52 . The role of genotypic makeup against response to doses of radiation was evident from the varying response of genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, a combined method of stepwise regression equation and correlation analysis was used to identify five morphological and yield indicators (plant height, spikelets per panicle, seed set, 1000-grain weight, and yield per plant) to evaluate low N tolerance (Hu et al, 2015). However, in sugarcane, a stepwise regression equation was only used in the estimation of cane yield (Luo et al, 2014). In our research, principle componential analysis, correlation analysis, stepwise regression analysis and path analysis were all carried out to evaluate the physiological and agronomic parameters for the selection of characteristic indictors to predict the NUE of sugarcane.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in photosynthetic rate, leaf area; tops, root and total biomass was found in sugarcane varieties (Basnayake, Jackson, Inman-Bamber, & Lakshmanan, 2012;Jackson et al, 2016;Li et al, 2017;Luo et al, 2014;Ramesh, 2000). In our study, significant variations were found in growth and dry matter parameters at both 60 and 120DAT, whereas the difference in A max just at 60DAT among Ni21 with NiF3, Ni9, and Ni17 at 60DAT.…”
Section: Discussionmentioning
confidence: 42%